STRATEGI DAN UPAYA PEMANFAATAN MEDIA SOSIAL DALAM BUDAYA BARU - Ayu Larasati; Heriyanti; Dina Sudarmika (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Social media is widely a common thing for everyday lives now, even some people cannot live without it. Basically, social media does not provide separation for its users, meaning that anyone can use social media, from children to adults. The purpose of this research is to examine social media in a new culture, as well as what strategies and efforts can be made so that social media can be utilized wisely. This research is a Qualitative Research, conducted on people aged 15-23 years. The method used is literature study, collecting data by finding sources and constructing them from various sources such as books, journals, and existing research. The results of the research show that social media can be utilized in a new culture.